Self, Society, and Repression in Babel: A Psychoanalytic Perspective - A.M. Iqbal (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2019)
As the prevailing studies tend to neglect how media depict the sociological question about the relationship between self and society and the dualism between pleasure and reality in modern society, this article examines this important issue by analyzing the award-winning film Babel by using a psychoanalytic perspective. Based on textual analysis of the film’s storylines, this article argues that Babel not only substantially represents the relationship between self and society, but also depicts the continuing tension and dualism between them. This is seen in the storylines of its characters that illustrate the relationship between sexual drives and social regulations. For the sake of social interests and cultural production, pleasure is repressed by external reality and sexuality is repressed through socially sanctioned sexual regulations. The self must attempt to balance between libidinal desire and social control to enter the normality of the social world.